Assessing HIV treatment literacy among men living with HIV in Mozambique: a mixed-methods study to identify insights, gaps and impact from the ‘Somos Iguais’ campaign - Marcos Chissano; Paul Bouanchaud; Mercy Murire; Nina Hasen; Montague Hermann; Micaela Rodrigrues; Yolanda Chongo (BMJ Open)
Objectives This study aimed to understand antiretroviral therapy (ART) adherence norms and beliefs among men living with HIV (MLHIV) in Mozambique, gauge the impact of misconceptions and harmful beliefs, evaluate perceived HIV service quality and assess the effectiveness of a behaviour change campaign (Somos Iguais), particularly among men aged 25–34 years.Design A mixed-methods, cross-sectional study using quantitative and qualitative approaches.Setting In Mozambique, over two million individuals live with HIV. This study was conducted in Maputo, Nampula and Sofala provinces.Participants The study comprised 10 focus group discussions with MLHIV aged 18–35 years and 58 indepth interviews with MLHIV aged 15–35 years across diverse subpopulations. A quantitative cross-sectional survey was completed by 1934 MLHIV aged 25–34 years.Intervention Population Services International developed a behaviour change campaign in 2020 aimed at reaching men age 25–34, who often remain undiagnosed or not virally suppressed.Outcome measure The study explores key aspects of HIV-related norms, behaviours and beliefs among people living with HIV, including high-risk subpopulations. These key aspects include misinformation, service quality gaps, perceived treatment benefits and the impact of the Somos Iguais campaign.Results Significantly more MLHIV who were on ART believed that HIV treatment reduces the risk of transmission compared with those who were not on ART (33% and 10%, respectively; p<0.001). Few, however, understood that undetectable viral loads prevent transmission. This lack of understanding is associated with self-stigma and diminished motivation to stay on ART. More than half (54%) of the survey participants agreed that people who are suspected of having HIV lose respect in their community. Surprisingly, our findings did not suggest that provider stigma hampers ART adherence; instead, concerns centred around clinic privacy while obtaining ART. Many MLHIV received HIV education only after diagnosis at the clinic, highlighting a significant community knowledge gap that intensified stigma and hampered treatment. The Somos Iguais behaviour change campaign resonated well with men already on ART, but less so with those not on treatment.Conclusion While the study highlights a positive trend in HIV treatment literacy among MLHIV, it showed persistent stigmatising attitudes in the wider community. Investments to enhance knowledge and counter misconceptions about HIV treatment, especially among men not reached by the Somos Iguais campaign, are essential in expanding and sustaining the number of MLHIV virally suppressed on ART. Safeguarding patient confidentiality in clinics is imperative to encourage and sustain ART adherence.